(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Poverty is a social pathology, that has plagued Brazil for a long time, causing many people to lack the bare minimum and live below the poverty line. Given this scenario, the problem of eradicating poverty in Brazil is the focus of this article. The study presented here will be based on the methodology of a bibliographical review, and will also include research carried out by entities that have looked into the problem presented, in order to point out indices that will corroborate the state of the art on poverty eradication programs in Brazil, taking sustainable development into account. Despite the existing public programs, more government action is needed to tackle poverty without neglecting sustainable development.